Fighting over the Bible : Jewish interpretation, sectarianism and polemic from Temple to Talmud and beyond - Kalimi, Isaac. (The Brill Reference Library of Judaism, 2017)
Fighting over the Bible explores the bitter conflicts between main stream Jews and their internal and external opponents, especially between particular Jewish groups such as Pharisees, Sadducees, Qumranites, Samaritans, Rabbanites and Karaites, as well as with Christians and Muslims regarding their interpretations of Jewish Scripture. The Hebrew Bible/Old Testament is an important sacred text for all branches of the Abrahamic faiths, but it has more often divided than unified them. This volume explores and exemplifies the roots of these interpretive conflicts and controversies and traces the rich exegetical and theological approaches that grew out of them. Focusing on the Jewish sources from the late Second Temple period through the high Middle-Ages, it illustrates how the study of the Bible filled the vacuum left by the Temple's destruction, and became the foundation of Jewish life throughout its long conflicted history.